Surgical Management of Retroperitoneal Liposarcoma: Opportunities for Multimodality Treatment, Including Systemic Therapy - Steven Sun; Kenneth Cardona; William W. Tseng (Cancer Medicine)
ABSTRACT Introduction Soft tissue sarcomas are a diverse group of rare cancers, with approximately 15%–20% found in the retroperitoneum. Liposarcomas (LPS) make up approximately half of all retroperitoneal (RP) sarcomas, with most cases classified as either well‐differentiated (WD) or dedifferentiated (DD). DD LPS is more aggressive, with a higher local recurrence rate and risk of distant metastasis compared to WD LPS. The purpose of this review is to outline surgical management of RP LPS and highlight the multimodal treatment strategies for both primary and recurrent disease, along with considerations for their effective implementation. Methods The current medical literature was reviewed for studies focused on retroperitoneal liposarcoma and its treatment with surgery, radiation, and chemotherapy. The data was interpreted and compiled in the context of expert clinical experience. Results Along with histopathologic analysis, tumor biology can inform patient prognosis. Surgery, the standard treatment for RP LPS, can be either curative or palliative. In primary disease, an attempt should be made to achieve wide surgical margins when feasible. Surgery for recurrent disease requires careful timing and an understanding of the potential benefit versus risk. Neoadjuvant radiation therapy can improve local control of RP LPS; however, data supporting the use of neoadjuvant chemotherapy are currently lacking. Conclusion Multimodality treatment of RP LPS is complex and requires consideration of tumor biology and extent of disease, along with individual patient characteristics. Multidisciplinary team collaboration is critical for improving outcomes in patients with RP LPS.